C–H-Functionalization logic guides the synthesis of a carbacyclopamine analog - Rabe, Sebastian; Moschner, Johann; Bantzi, Marina; Heretsch, Philipp; Giannis, Athanassios (Beilstein Journal of Organic Chemistry, 2014)
The chemical synthesis of carbacyclopamine analog 2, a cyclopamine analog with an all-carbon E-ring, is reported. The use of C–H-functionalization logic and further metal-catalyzed transformations allows for a concise entry to this new class of acid-stable cyclopamine analogs.
Keywords: cyclopamine; C–H-functionalization; hedgehog signaling pathway; natural products; steroidal alkaloids

(untitled) - Keeler, R. F. (Phytochemistry, 1968)

(untitled) - Keeler, R. F. (Teratology, 1970)

(untitled) - Beachy, P. A.; Karhadkar, S. S.; Berman, D. M. (Nature, 2004)

(untitled) - Taipale, J.; Beachy, P. A. (Nature, 2001)

(untitled) - Hidalgo, M.; Maitra, A. (N. Engl. J. Med., 2009)

(untitled) - Dierks, C.; Grbic, J.; Zirlik, K.; Beigi, R.; Englund, N. P.; Guo, G.-R.; Veelken, H.; Engelhardt, M.; Mertelsmann, R.; Kelleher, J. F.; Schultz, P.; Warmuth, M. (Nat. Med., 2007)

(untitled) - Hedge, G. V.; Munger, C. M.; Emanuel, K.; Joshi, A. D.; Greiner, T. C.; Weisenburger, D. D.; Vose, J. M.; Joshi, S. S. (Mol. Cancer Ther., 2008)

(untitled) - Kawahara, T.; Kawaguchi-Ihara, N.; Okuhashi, Y.; Itoh, M.; Nara, N.; Tohda, S. (Anticancer Res., 2009)

(untitled) - Heretsch, P.; Tzagkaroulaki, L.; Giannis, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Heretsch, P.; Tzagkaroulaki, L.; Giannis, A. (Bioorg. Med. Chem., 2010)
And references cited therein.

(untitled) - Giannis, A.; Heretsch, P.; Sarli, V.; Stößel, A. (Angew. Chem., Int. Ed., 2009)

(untitled) - Heretsch, P.; Büttner, A.; Tzagkaroulaki, L.; Zahn, S.; Kirchner, B.; Giannis, A. (Chem. Commun., 2011)

(untitled) - Moschner, J.; Chentsova, A.; Eilert, N.; Rovardi, I.; Heretsch, P.; Giannis, A. (Beilstein J. Org. Chem., 2013)

(untitled) - Tremblay, M. R.; Nevalainen, M.; Nair, S. J.; Porter, J. R.; Castro, A. C.; Behnke, M. L.; Yu, L.-C.; Hagel, M.; White, K.; Faia, K.; Grenier, L.; Campbell, M. J.; et al. (J. Med. Chem., 2008)

(untitled) - Tremblay, M. R.; Lescarbeau, A.; Grogan, M. J.; Tan, E.; Lin, G.; Austad, B. C.; Yu, L.-C.; Behnke, M. L.; Nair, S. J.; Hagel, M.; White, K.; Conley, J.; et al. (J. Med. Chem., 2009)

(untitled) - Zhang, Z.; Baubet, V.; Ventocilla, C.; Xiang, C.; Dahmane, N.; Winkler, J. D. (Org. Lett., 2011)

(untitled) - Winkler, J. D.; Isaacs, A.; Holderbaum, L.; Tatard, V.; Dahmane, N. (Org. Lett., 2009)

(untitled) - Taipale, J.; Chen, J. K.; Cooper, M. K.; Wang, B.; Mann, R. K.; Milenkovic, L.; Scott, M. P.; Beachy, P. A. (Nature, 2000)

(untitled) - Wang, Y.; Zhou, Z.; Walsh, C. T.; McMahon, A. P. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Pearse, R. V., II; Collier, L.S.; Scott, M. P.; Tabin, C. J. (Dev. Biol., 1999)

(untitled) - Wen, X.; Lai, C. K.; Evangelista, M.; Hongo, J.-A.; de Sauvage, F. J.; Scales, S. J. (Mol. Cell. Biol., 2010)

(untitled) - Pan, Y.; Bai, C. B.; Joyner, A. L.; Wang, B. (Mol. Cell. Biol., 2006)

(untitled) - Wang, B.; Fallon, J. F.; Beachy, P. A. (Cell, 2000)

(untitled) - Wilson, S. R.; Strand, M. F.; Krapp, A.; Rise, F.; Petersen, D.; Krauss, S. (J. Pharm. Biomed. Anal., 2010)
See for a proposed mechanism of the decomposition of cyclopamine. For a discussion of the molecular orbitals involved in the process, see ref. [12.]

(untitled) - Schönecker, B.; Zheldakova, T.; Lange, C.; Günther, W.; Görls, H.; Bohl, M. (Chem.–Eur. J., 2004)

(untitled) - Schönecker, B.; Zheldakova, T.; Liu, Y.; Kötteritzsch, M.; Günther, W.; Görls, H. (Angew. Chem., Int. Ed., 2003)

(untitled) - Schönecker, B.; Lange, C.; Zheldakova, T.; Günther, W.; Görls, H.; Vaughan, G. (Tetrahedron, 2005)

(untitled) - Ojima, I.; Chen, J.; Sun, L.; Borella, C. P.; Wang, T.; Miller, M. L.; Lin, S.; Geng, X.; Kuznetsova, L.; Qu, C.; Gallager, D.; Zhao, X.; et al. (J. Med. Chem., 2008)

(untitled) - Fernholz, E.; Ruigh, W. L. (J. Am. Chem. Soc., 1940)

(untitled) - Wallis, E. S.; Fernholz, E.; Gephart, F. T. (J. Am. Chem. Soc., 1937)

(untitled) - Rotulo-Sims, D.; Prunet, J. (Org. Lett., 2002)

(untitled) - Nakamura, E.; Yoshikai, N.; Yamanaka, M. (J. Am. Chem. Soc., 2002)

(untitled) - Doyle, M. P.; Duffy, R.; Ratnikov, M.; Zhou, L. (Chem. Rev., 2010)

(untitled) - Heretsch, P.; Rabe, S.; Giannis, A. (J. Am. Chem. Soc., 2010)

(untitled) - Abbiati, G.; Arcadi, A.; Bianchi, G.; Di Giuseppe, S.; Marinelli, F.; Rossi, E. (J. Org. Chem., 2003)